Efektivitas Sanitizer Komersial Berbasiskan Asam Perasetat terhadap Biofilm Bacillus cereus - N. Eliza; R. Dewanti-Hariyadi; S. Nurjanah (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Bacillus cereus is known to have the ability to adhere and form biofilms on the surface of stainless steel that causes problems in the food industries. Bacterial biofilms generally can increase resistance to sanitizer treatment. This study aimed to evaluate the ability of peracetic acid-based commercial sanitizer to inactivate B. cereus biofilm on stainless steel (SS) surfaces. Biofilm of B. cereus ATCC 10876 was developed on SS surfaces and treated with 7 commercial peracetic acid-based sanitizers at their recommended dosages. Two sanitizers, i.e. B (peracetic acid and QAC) and F (peracetic acid and acidified water) showing the ability to inactivate B. cereus on solid media at concentration of 200, 400, and 800 ppm were further tested on biofilms with contact times of 1, 3, and 5 minutes. The 48 hours biofilms B. cereus contained 2.78-3.78 CFU/cm2. Both sanitizers B and F had significant effects in inactivating B. cereus biofilm. In general, sanitizer B could reduce more biofilm bacteria at any contact time than sanitizer F. Use of 200 ppm of sanitizer B or F 5 minutes could inactivate 3.04 log CFU/cm2 and 2.68 log CFU/cm2 biofilm, respectively. Exposure of B. cereus biofilm to peracetic acid-based sanitizer resulted in the damage of the extracellular matrix of the biofilms. This study showed that commercial sanitizers containing peracetic acid and quaternary ammonium compounds were effective in inactivating B. cereus biofilms.